Peningkatan Aktivitas dan Hasil Belajar Siswa Kelas XI MIA 1 MAN 1 Banjarmasin pada Materi Larutan Penyangga Menggunakan Model Problem Based Learning Berbantuan Media Audiovisual - Anwar, Anwar Anwar (Jurnal PTK dan Pendidikan, 2018)
Learning using appropriate media will provide optimal results for student’s understanding of the material being studied. PBL is usually done with a group approach by emphasizing the development of the group's skills to take decisions, discuss, solve problems, agreement, and leadership of the group. Activities and learning outcomes of students on learning of buffer material materials using PBL model aided in audiovisual media in class XI MIA 1 MAN 1 Banjarmasin. Student learning activities using PBL model (Problem Based Learning) aided audiovisual media increased. The completeness of student learning outcomes in the classical increased by 27,03%, seen from the results of cycle I of 59,46% and on the second cycle of 86,49%.